Principles of Building an Effective Regional Multilevel Model of Oncological Care - M.Yu. Mostovoy; R.A. Murashko; M.G. Leonov (Effective Pharmacotherapy, 2026)
The implementation of the current medical care order required structural changes in the oncology service. The object of the study was medical organizations providing medical care in the oncology profile, operating in the Krasnodar Territory. Further development of a regional multi-level model for providing oncological care, an increase in the number of outpatient oncological care centers, and the creation of seamless routing for diagnostics and anti-tumor treatment will contribute to increased access to specialized care, including its closer availability to the rural population.